Molecular epidemiology of AY.28 and AY.104 delta sub-lineages in Sri Lanka - Ranasinghe, D; Jayathilaka, DJ; Jeewandara, C; Gunasinghe, D; Ariyaratne, D; Jayadas, TTP; Kuruppu, H; Wijesinghe, A; Bary, FF; Madhusanka, D; Pushpakumara, PD; Guruge, D; et al. (Frontiers Media, 2022)
Background: The worst SARS-CoV-2 outbreak in Sri Lanka was due to the two Sri Lankan delta sub-lineages AY.28 and AY.104. We proceeded to further characterize the mutations and clinical disease severity of these two sub-lineages.